Generic Quality of Life in Persons With Hearing Loss: A Review of the Recent Literature. Issue 9 (October 2018) - Brodie, Arjuna; Ray, Jaydip
Abstract : Background: It is unknown whether persons with hearing loss (HL) have reduced generic quality of life (QoL) and to what extent a hearing aid (HA) might improve QoL. The main aim of the study was to review studies about the relationship between HL and QoL. A supporting aim was to study the association between distress and HL. Methods: Literature databases (CINAHL, Pub Med, and Web of Science) were searched for relevant articles published from January 2000 to March 17, 2016. A primary search was performed regarding the relationship between HL, HA, and QoL (search one) followed by a supporting search about the relationship between distress/mood/anxiety and HL (search two). After removing duplications and screening the titles of the articles, the abstracts of the remaining articles were read and those that met the inclusion criteria were included. Results: The two searches yielded a total of 4, 188 journal articles. Twenty journal articles were included in the present review: 13 from search one, and 7 from search two. The literature shows distressed persons tend to have a lowered generic QoL. Some studies suggest an improved generic QoL following the use of HA. Other studies suggest that HA use is one of several possible factors that contribute to improved generic QoL. Conclusion: Most of the studies suggest that HL is associated with reduced generic QoL. Using HA seems to improve general QoL. Further research is needed to explore the relationship between HL and generic QoL, in addition to the importance of influencing variables on this relationship.